PENINGKATAN PRODUK UMKM JAMU “SARI MINUMAN” MELALUI PENGEMBANGAN KEMASAN MENARIK DENGAN CANVA - Fatimah, Dewi; Lorenza, Dea Agusti; Walidaini, Muhamad Birul; Harpepen, Andi (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
UMKM “Sari Minuman” is a local business that produces various types of traditional herbal medicine such as turmeric, tamarind turmeric, beras kencur, and pegal linu. Although it has quality products and is beneficial for health, this UMKM faces challenges in the visual aspect of the product, especially the packaging design which is still plain and does not have a strong brand identity. This community service aims to increase the competitiveness and selling value of the product through the development of attractive packaging designs using the Canva application. The activity methods include observation, planning, graphic design training, and direct assistance in the field. The results of this activity show an increase in the understanding of UMKM actors regarding the importance of visual identity and the ability to use digital design tools independently. This initiative is expected to strengthen product branding and increase the appeal to consumers of traditional herbal medicine.